Effects of exercise countermeasures on multisystem function in long duration spaceflight astronauts - Jessica M. Scott; Alan H. Feiveson; Kirk L. English; Elisabeth R. Spector; Jean D. Sibonga; E. Lichar Dillon; Lori Ploutz-Snyder; Meghan E. Everett (npj Microgravity, 2023)
Abstract Exercise training is a key countermeasure used to offset spaceflight-induced multisystem deconditioning. Here, we evaluated the effects of exercise countermeasures on multisystem function in a large cohort (N = 46) of astronauts on long-duration spaceflight missions. We found that during 178 ± 48 d of spaceflight, ~600 min/wk of aerobic and resistance exercise did not fully protect against multisystem deconditioning. However, substantial inter-individual heterogeneity in multisystem response was apparent with changes from pre to postflight ranging from −30% to +5%. We estimated that up to 17% of astronauts would experience performance-limiting deconditioning if current exercise countermeasures were used on future spaceflight missions. These findings support the need for refinement of current countermeasures, adjunct interventions, or enhanced requirements for preflight physiologic and functional capacity for the protection of astronaut health and performance during exploration missions to the moon and beyond.